A Case of Group A Streptococcal Meningitis in an Adult - Andrew LS Pattullo; Eric J Bow (Canadian Journal of Infectious Diseases)
Group A streptococci are an important cause of soft tissue infections but have rarely been reported as the cause of pyogenic meningitis since the advent of antibiotics. A case of group A streptococcal meningitis in an adult is presented along with a review of similar cases reported in the literature. This case serves to illustrate the virulent nature of this pathogen in infections of the meninges, the potential for associated complications, and the need for rapid diagnosis and appropriate treatment. The source of infection in this and many other cases in the literature is the upper respiratory tract. The case presented responded well to antibiotics but resulted in permanent auditory-vestibular dysfunction.